Service Delight and Brand Love: Its’ Impact on Premium Price and Word-of-Mouth - Pereira, Inês Veiga (2023)
Organizations have come to realize that beyond satisfaction, customers desire an emotional attachment with brands, developing true love or hate feelings towards them. Now, can this feeling be visible in the intangibility of the services sector? This research has focused on Brand Love and its’ relationship with customer delight when services are concerned. Three specific dimensions were explored: the physical environment where the service takes place, the innovation factor in the service as well as the employees that provide it. The methodology adopted for this research has consisted of the construction of a structural equations model conveyed by a questionnaire. By analyzing the obtained results using SmartPLS software, we have found that in a service's context, Brand Love can also be verified. This is possible due to customer delight regarding the service, visible mostly in the dimension of the physical surrounding where the service is provided. We have verified that this love for the brand can generate positive word-of-mouth, as well as a willingness to pay a superior cost for the same service. These results reinforce the importance that service brands should place on their tangible assets to generate their own brand ambassadors while growing their profitability margins. DOI: https://doi.org/10.54663/2182-9306.2023.sn13.156-176